Сontrolling parameters determining technological properties of a helicon discharge system - Semenyuk, V.F.; Virko, V.F.; Korotash, I.V.; Osipov, L.S.; Polotsky, D.Yu.; Rudenko, E.M.; Slobodyan, V.M.; Shamrai, K.P. (Вопросы атомной науки и техники, 2013)
In experiments on two helicon sources driven by a planar antenna, it is shown that the plasma density in the drift chamber and the energies and density of the ion flux onto the substrate holder can be effectively controlled by changing the local magnetic field and the holder potential.